HUBUNGAN UNDANG-UNDANG PERSEROAN TERBATAS DENGAN PERAN PERUSAHAAN DALAM PELAYANAN MASYARAKAT - Bachtiar Kemal Harahap; Pandri Zulfikar; Teddy T Pingak; Akhmad Faishal; M Zaenuddin Ibrahim (CV. Lafadz Jaya, 2026)
Law Number 40 of 2007 concerning Limited Liability Companies (LLC Law) is the main legal foundation for regulating corporate legal entities in Indonesia. Amid rapid economic development, the role of companies is no longer limited to profit-seeking alone, but has evolved into entities that have social responsibility towards society. This study aims to analyze the relationship between the provisions of the LLC Law and the role of companies in public service, identify legal gaps, and formulate an ideal legal construction. The method used is normative legal research with statutory, conceptual, and comparative approaches. The results indicate that the LLC Law has accommodated the role of companies in public service through the regulation of Corporate Social Responsibility (CSR) in Article 74, annual reporting obligations, and protection of stakeholders. However, its implementation still faces challenges related to normative inconsistency, limited scope of CSR obligations, and weak law enforcement. This study recommends regulatory harmonization, expansion of CSR obligations, and strengthening of oversight mechanisms to enhance the effectiveness of the corporate role in public service.